Systematic review: early detection of post stroke depression symptoms - Rinancy, Hariet (Journal of health research and technology, 2024)
The importance of early detection of early symptoms of post-stroke depression (PSD) is to prevent psychosocial problems in stroke patients. Post-stroke depression is an abnormal psychological symptom in someone who has suffered a stroke. PSD is a complication of stroke with a prevalence of 9-60% which is characterized by mood abnormalities, self-blame, sadness and depression. PSD can hinder the recovery of neurological function and daily activities of stroke patients, thus making the condition of stroke sufferers worse. The aim of the research is for early detection of PSD symptoms and PSD intervention. Method: systematic review using the literature search method with systematic reviews (PRISMA) as the standard for conducting systematic reviews. Article searches were carried out in electronic databases such as Science Direct, Pubmed and Proquest, Google Scholar using the keywords Depression, Diagnosis, Intervention and stroke. The criteria for selected articles are 1) published in 2019-2023 2) full text 3) articles in English and Indonesian. Articles were selected according to the criteria and a total of 6 articles out of 5312 articles were obtained with PRISMA. This research found that there are many types of instruments for early detection of post-stroke depression symptoms and appropriate intervention according to the level of depression. The high prevalence of PSD is due to the care giver not detecting early symptoms of depression, which worsens the condition of stroke sufferers. Most stroke patients experience severe depression. The researcher's suggestion is that there is a need for a program to provide education to stroke patients and their families in recognizing the early signs and symptoms of PSD, so that they can prevent the occurrence of depression in both clinical and community settings.